2018
DOI: 10.1101/280891
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

GABA promotes survival and axonal regeneration in identifiable descending neurons after spinal cord injury in larval lampreys

Abstract: Phones : +34 881816949 and +34 881816946 Emails: anton.barreiro@usc.es and mcelina.rodicio@usc.es Running title: GABA promotes regeneration after spinal cord injury peer-reviewed) is the author/funder. All rights reserved. No reuse allowed without permission.The copyright holder for this preprint (which was not . http://dx.doi.org/10.1101/280891 doi: bioRxiv preprint first posted online Mar. 12, 2018; 2 AbstractIn mammals, spinal cord injury (SCI) causes permanent disability. The poor regenerative capacit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 70 publications
(90 reference statements)
1
4
0
Order By: Relevance
“…Specifically, this treatment led to a significant increase in the regeneration of individually identifiable descending neurons of the lamprey brainstem. This is in agreement with our previous results showing improved axon regeneration after baclofen or GABOB treatments after SCI in lampreys (Romaus-Sanjurjo et al, 2018a). So, the Notch signaling pathway appears to be of crucial importance in the regulation of axon regrowth after SCI in lampreys.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Specifically, this treatment led to a significant increase in the regeneration of individually identifiable descending neurons of the lamprey brainstem. This is in agreement with our previous results showing improved axon regeneration after baclofen or GABOB treatments after SCI in lampreys (Romaus-Sanjurjo et al, 2018a). So, the Notch signaling pathway appears to be of crucial importance in the regulation of axon regrowth after SCI in lampreys.…”
Section: Discussionsupporting
confidence: 93%
“…In previous work, we showed that both GABA and baclofen promote axon regeneration after a complete SCI in lampreys (Romaus-Sanjurjo et al, 2018a). Here, we aimed to identify new genes involved in axon regeneration in lampreys that might be regulated by GABAergic signaling.…”
Section: Rna-seq Differential Expression Analysesmentioning
confidence: 96%
See 1 more Smart Citation
“…18 Interestingly, recent work of our group has shown that endogenous GABA promotes axonal regeneration of identifiable reticulospinal neurons following SCI in lampreys. 19 The beneficial effects of GABA appear to be mainly mediated through the activation of GABAB receptors in injured neurons; 19 although, recent work has also shown that the activation of GABAA receptors by muscimol inhibits caspase activation in identifiable neurons after SCI in lampreys. 20 Taken together, these data prompted us to study the possible effect of taurine in axon regeneration after SCI in lampreys.…”
Section: Main Textmentioning
confidence: 99%
“…54 GABA/baclofen (a GABA B agonist) can reduce the caspase activity of brain neurons at 2 weeks after the complete transection of the lamprey's spinal cord, thereby inhibiting the progression of apoptosis and promoting the survival/regeneration of descending projections. 55,56 Further RNA-sequencing results revealed that GABA or baclofen treatment substantially down-regulated the HES gene and decreased the activation of the Notch signaling pathway after SCI, thus revealing a novel therapeutic target that can inhibit g-secretase activity to promote axon regeneration. 57 These studies from lamprey SCI models revealed the effects of SCI on brain structure and proposed several (and are still expanding) drugs to alleviate the death/atrophy of descending projection neurons caused by degeneration.…”
Section: Introductionmentioning
confidence: 99%